2013
DOI: 10.1016/j.jaci.2013.06.035
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 confers resistance to IL-27–mediated suppression on CD4+ T cells by impairing signal transducer and activator of transcription 1 signaling

Abstract: Background Th2 cells play a critical role in the pathogenesis of allergic asthma. Established Th2 cells have been shown to resist reprogramming into Th1 cells. The inherent stability of Th2 cells poses a significant barrier to treating allergic diseases. Objective We sought to understand the mechanisms by which CD4+ T cells from asthmatic patients resist the IL-27-mediated inhibition. Methods We isolated and cultured CD4+ T cells from both healthy individuals and allergic asthmatic patients in order to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…In particular, GATA3 expression was positively correlated with pSTAT6, which indicated a certain regulatory relationship between pSTAT6 and GATA3. As we know, pSTAT6 can be regulated by many factors in the body and change in pSTAT6 correlates with many diseases (Batra et al, 2004;Thunberg et al, 2010;Chen et al, 2013;Yao et al, 2013;Irvin et al, 2014). Our present results prove that after boswellic acid treatment, GATA3 is downregulated following a decrease in pSTAT6, which indicates that boswellic acid may improve the asthma phenotype by inhibiting pSTAT6 and thus influencing GATA3 expression (Tachdjian et al, 2010).…”
Section: Discussionsupporting
confidence: 69%
“…In particular, GATA3 expression was positively correlated with pSTAT6, which indicated a certain regulatory relationship between pSTAT6 and GATA3. As we know, pSTAT6 can be regulated by many factors in the body and change in pSTAT6 correlates with many diseases (Batra et al, 2004;Thunberg et al, 2010;Chen et al, 2013;Yao et al, 2013;Irvin et al, 2014). Our present results prove that after boswellic acid treatment, GATA3 is downregulated following a decrease in pSTAT6, which indicates that boswellic acid may improve the asthma phenotype by inhibiting pSTAT6 and thus influencing GATA3 expression (Tachdjian et al, 2010).…”
Section: Discussionsupporting
confidence: 69%
“…Previous in vitro studies have suggested that STAT1 and STAT3 are the main signaling pathways controlling the effects of IL‐27 on epithelial cells (Diegelmann, Olszak, Goke, Blumberg, & Brand, ). The STAT1 pathway is critical for IL‐27 signaling, which can upregulate ICAM‐1 and T‐bet expression in naive CD4+ T cells leading to Th1 differentiation and inhibition of Th2 differentiation (Z. Chen et al, , ; Kamiya et al, ; Owaki et al, ; Takeda et al, ). In addition, JAK/STAT independent, p38/MAPK signaling by IL‐27 has been reported, which ultimately leads to IFN‐γ secretion by activating T‐bet.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recent research has indicated that IL-27 can’t inhibit already differentiated Th17 cells [ 12 ], and our previous study indicated CD4 + T cells from asthmatic patients resisted IL-27-mediated suppression of IL-4 production [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%